2002
DOI: 10.1002/app.10441
|View full text |Cite
|
Sign up to set email alerts
|

Phenol‐modified polypropylenes as adhesion promoters in glass fiber–reinforced polypropylene composites

Abstract: This publication is based on research work done on functional phenolmodified polypropylenes (PPs) as adhesion promoters in glass fiber-reinforced PP composites. The glass fiber roving was first impregnated with different combinations of functional polymers and polypropylene in a melt impregnation die attached to an extruder to obtain prepreg. The prepreg was then tested in many ways both macro-and micromechanically. The tests included notched tensile tests, optical and electron microscopy, and DMTA (dynamic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…To improve the adhesion between glass fiber and thermoplastic resin, compatibilizers like maleic anhydride grafted polypropylene (PP), acrylic acid grafted PP, dendritic polymers, and phenol grafted PP are generally used in small proportions [9]. Reliable control of the degree of adhesion between fiber and matrix is required for using the composite as a structural material.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the adhesion between glass fiber and thermoplastic resin, compatibilizers like maleic anhydride grafted polypropylene (PP), acrylic acid grafted PP, dendritic polymers, and phenol grafted PP are generally used in small proportions [9]. Reliable control of the degree of adhesion between fiber and matrix is required for using the composite as a structural material.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research work is reported these days on injection molding of long fiber reinforced thermoplastic pellets to make long fiber composites [8][9][10][11][12][13]. In order to improve the adhesion between glass fiber and thermoplastic resin, coupling agents like maleic anhydride grafted polypropylene, acrylic acid grafted polypropylene, dendritic polymers, and phenol grafted polypropylene [14] were generally used in small proportions. Reliable control of the degree of adhesion between fiber and matrix is required for using the composite as a structural material.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much attention has been paid to compatibilising technology using polymeric compatibilisers, which has proved to be an effective way to modify polymer composites. [24][25][26][27][28][29][30][31] Using reactive polar monomers, such as acrylic acid, to cover the surface of the filler, and in situ synthesise functionalised polymeric coupling agent in the preparation process of materials is more effective in improving the interfacial adhesion between filler and matrix. The polymeric coupling agent can not only improve the dispersion of the filler in the polymeric matrix, but also strengthen the adhesion between the filler and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%